Tinjauan Sistematis: Peran Kultur Hanging Drop 3D terhadap Ekspresi OCT4 dan NANOG pada Sel Punca Mesenkimal Tali Pusat dengan Suplementasi PRP dan FBS - Muhammad Faishal Budi Utomo; Wahyunia L. Septiana; Sastia Winda Astuti; Helsy Junaidi (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2026)
Abstract Systematic Review: The Role of Three-Dimensional Hanging Drop Culture in OCT4 and NANOG Expression in Umbilical Cord-Derived Mesenchymal Stem Cells Supplemented with PRP and FBS Umbilical cord-derived mesenchymal stem cells (UC-MSCs) have considerable potential in regenerative medicine due to their multipotent capacity, high proliferative ability, and self-renewal properties. Three-dimensional (3D) hanging drop culture has been shown to promote spheroid formation that closely mimics the in vivo microenvironment, thereby supporting stemness maintenance and enhancing the expression of pluripotency-related genes, such as OCT4 and NANOG. However, the use of Fetal Bovine Serum (FBS) as a culture supplement remains limited by concerns regarding immunogenicity and the potential transmission of biological contaminants, highlighting the need for xeno-free alternatives such as Platelet-Rich Plasma (PRP). This systematic review aimed to evaluate the effects of PRP and FBS supplementation on the biological characteristics of UC-MSCs cultured using the 3D hanging drop method. A literature search was conducted using PubMed, ScienceDirect (Elsevier), and Google Scholar databases for studies published between 2015 and 2025, employing keywords related to UC-MSCs, 3D hanging drop culture, PRP, FBS, OCT4, and NANOG. Eligible studies were critically analyzed based on methodological quality and relevance to the review objectives. The findings indicate that 3D hanging drop culture enhances spheroid formation, preserves cell viability, and increases the expression of stemness markers OCT4 and NANOG compared with conventional two-dimensional culture. Several studies also reported that PRP supplementation supports cell proliferation and viability while maintaining pluripotency-related gene expression at levels comparable to or higher than those achieved with FBS. These findings suggest that PRP represents a promising xeno-free alternative for maintaining the stemness of UC-MSCs and supporting their future clinical applications in regenerative medicine. Keywords: umbilical cord-derived mesenchymal stem cells, 3D hanging drop culture, platelet-rich plasma, fetal bovine serum, OCT4, NANOG.